2006
DOI: 10.1196/annals.1354.031
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Accelerated Cell Aging in the Werner Syndrome

Abstract: In the Werner syndrome (WS) fibroblasts have an increased life span and growth rate when treated with the p38 inhibitor SB203580. Additionally, the cellular morphology reverts to that seen in young normal fibroblasts. The p38 pathway is activated in young WS cells, associated with high levels of p21(WAF1) leading to cell cycle arrest, and is suppressed by SB203580. As these changes are also seen in telomerized WS cells, these data show that the growth problems seen in WS cells, and perhaps the accelerated in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 11 publications
(31 reference statements)
0
28
0
Order By: Relevance
“…There is no effective treatment for WS. It has been reported that p38 MAPK activation causes stress-induced premature senescence (SIPS) and p38 selective inhibitor molecule SB203580 may increase the growth and life span of fibroblasts (28,29). This data suggest that further studies are necessary to identify new targets for the treatment of premature aging.…”
Section: Discussionmentioning
confidence: 97%
“…There is no effective treatment for WS. It has been reported that p38 MAPK activation causes stress-induced premature senescence (SIPS) and p38 selective inhibitor molecule SB203580 may increase the growth and life span of fibroblasts (28,29). This data suggest that further studies are necessary to identify new targets for the treatment of premature aging.…”
Section: Discussionmentioning
confidence: 97%
“…For this reason "natural" ageing has also been described as a consequence of chronic inflammation. In fact the term "Inflame-Aging" has been coined based on experimental evidence that has been demonstrated in the context of characterizing the molecular events in the classical Werner´s progeria syndrome [91,92]. MSC in vivo recruitment to the synovial surface has recently been demonstrated in patients with osteoarthritis [93].…”
Section: Immunomodulationmentioning
confidence: 99%
“…Intrinsic factors include telomeres which are shortened with each replication cycle until they reach a critical short length at which time they signal for apoptosis [4]. The effect of telomere shortening on aging is supported by the fact that they are shorter in patients with premature aging syndromes such as Werner syndrome [5]. DNA damage and defects in DNA repair mechanisms are also thought to play a role in aging.…”
Section: Introductionmentioning
confidence: 99%